Comparison of the Modified Centers for Disease Control and Prevention 2019-Novel Coronavirus Real-Time RT-PCR Method for Detection of Infectious and Heat-Inactivated Virus on Stainless Steel. (2nd April 2021) - Brunelle, Sharon L; Bird, Patrick M; Boone, Jeremy; Nelson, Maria; Johnson, Zerlinde; Coates, Scott
Abstract: Background: Infectious Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) was used in the validation of methods for detection of SARS-CoV-2 on stainless-steel surfaces in the AOAC Research Institute Emergency Response Validation project. Handling infectious virus requires Biosafety Level (BSL)-3 facilities. Objective: To compare the recovery and detection of infectious and heat-inactivated (HI; 65°C for 30 min) SARS-CoV-2 from stainless steel by the modified US Centers for Disease Control and Prevention (CDC) 2019-Novel Coronavirus (2019-nCoV) Real Time Reverse Transcription Polymerase Chain Reaction (RT-PCR) Diagnostic Panel . Method: Viral stocks were diluted in viral transport medium (VTM) and deposited onto stainless-steel test areas at 2 × 10 3 and 2 × 10 4 genomic copies for low and high, respectively. Test areas were sampled and aliquots of the resulting test solutions analyzed by RT-qPCR according to the CDC method. Results were analyzed by probability of detection (POD) statistics. Results: The low level, where fractional positive results (25–75%) are expected, yielded PODI = 0.80 (0.58, 0.92) for the infectious virus and PODHI = 0.15 (0.05, 0.36) for the HI virus. The bias, dPODHI = −0.65 (−0.80, −0.35), demonstrated a statistical difference between infectious and HI virus detection. No difference was observed at the high inoculation level. Conclusions: Despite the statistical difference observed, the use of the HI virus is a viable alternative for matrix extension studies using a method comparison study design. Highlights : The use of HI SARS-CoV-2 can mitigate the need for a BSL-3 facility for matrix extension validation of alternative methods in SARS-CoV-2 studies. Highlights: The use of HI SARS-CoV-2 can mitigate the need for a BSL-3 facility for matrix extension validation of alternative methods in SARS-CoV-2 studies.